CLINICAL INDICATORS OF DYSPEPSIA IN CALVES - Axmadov, A.I. (Research Focus International Scientific Journal, 2026)
This article examines the main clinical signs of dyspepsia in calves, the causes of the disease, and the mechanisms of its development. The study analyzed the main symptoms observed in calves with dyspepsia, including fever, diarrhea, dehydration, general weakness, and decreased feed intake. Furthermore, in severe forms of the disease, significant clinical changes were identified, such as the appearance of blood and mucus in the stool, as well as electrolyte imbalances.